Development and Evaluation of a Digital Health Intervention for Substance Use Reduction in Young Refugees With Problematic Use of Alcohol and/or Cannabis—Study Protocol for a Single-Armed Feasibility Trial - Fischer, Laura Charlotte; Kölligan, Vera; Wieland, Nuri; Klein, Michael (Frontiers in Public Health, 2021)
Background: Refugee populations are at substantial risk of developing substance use disorder (SUD) and other mental health disorders. At the same time, refugee populations face numerous barriers to accessing mental health services. Digital health interventions (DHI) can address some of these issues, as emerging evidence indicates that digital interventions offer an effective, low-cost alternative with high accessibility and similar efficacy as standard SUD prevention programs. As an add-on to traditional services, they further present a viable approach to the lack of personnel available for foreign language communication in preventive and therapeutic settings. The present study this aims to develop and evaluate a DHI for the reduction of substance use for young refugees with problematic use of alcohol and or cannabis. The intervention will be implemented in a smartphone app, translated into Arabic, English, Farsi, German, and Pashto, and is to be used stand-alone. It is based on methods from cognitive-behavioral therapy, contains culturally adapted elements, provides practical information on how to deal safely with alcohol and cannabis, and motivates behavior change through increased self-reflection and behavioral, cognitive, and emotional skills-training in interactive exercises. Methods: We conduct a single-armed feasibility trial among 150 young refugees with problematic use of alcohol and / or cannabis. Participants will receive a digital screening and digital health intervention for the reduction of problematic substance use, carried out over a 4-week time frame. The primary outcomes are the intervention’s feasibility and the target population’s acceptance of the intervention. The secondary outcome is a change in substance use post-intervention from baseline. Measurements are taken pre-intervention (baseline), post-intervention (after 4 weeks), and at 3- and 6-month follow-ups. We expect the intervention to be feasible and accepted by the target group. Discussion: The present study will establish to what degree the digital intervention is feasible and accepted by the target group. The evaluation of an easily accessible, feasible, and accepted intervention may impact refugees’ mental health and health-related consequences. It aims at overcoming barriers to preventive health care in the substance use field for underserved refugee populations as a tool within a larger set of urgently needed interventions.